Clinical characteristics and cytokine biomarkers in patients with chronic graft‐vs‐host disease persisting seven or more years after diagnosis. Issue 4 (25th January 2020) - Goklemez, Sencer; Im, Annie P.; Cao, Liang; Pirsl, Filip; Steinberg, Seth M.; Curtis, Lauren M.; Mitchell, Sandra A.; Cowen, Edward W.; Baruffaldi, Judy; Rose, Jeremy; Mays, Jacqueline; Ostojic, Alen; et al.
Abstract: Chronic graft‐versus‐host disease (cGVHD) is the leading late complication after allogeneic hematopoietic stem cell transplantation (HSCT). Many patients receive multiple lines of systemic therapy until cGVHD resolves, but about 15% remain on systemic treatment for more than 7 years after cGVHD diagnosis. This study describes the clinical and biological factors of patients who present with cGVHD persisting for ≥7 years (persistent cGVHD). Patients with persistent cGVHD (n = 38) and those with cGVHD for <1 year (early cGVHD) (n = 83) were enrolled in a prospective cross‐sectional natural history study. Patients in the persistent cGVHD group were a median of 10.2 years from cGVHD diagnosis (range 7‐27 years). Fifty‐eight percent of persistent cGVHD patients (22/38) were receiving systemic immunosuppression, compared to 88% (73/83) in the early cGVHD group. In multivariable analysis, bone marrow (BM) stem cell source, presence of ENA autoantibodies, higher NIH lung score, higher platelet counts, and higher IgA levels were significantly associated with persistent cGVHD. A high sensitivity panel of serum biomarkers including seven cytokines diagnostic for cGVHD was analyzed and showed significantly lower levels of BAFF and CXCL10 in patients with persistent cGVHD. In conclusion, standardly accepted clinical measures of disease severity may not accurately reflect disease activity in patients with persistent cGVHD. However, many patients with persistent cGVHD are still receiving systemic immunosuppression despite lacking evidence of disease activity. Development of reliable clinical biomarkers of cGVHD activity may help guide future systemic treatments.